tappAS: a comprehensive computational framework for the analysis of the functional impact of differential splicing - Lorena de la Fuente; Ángeles Arzalluz-Luque; Manuel Tardáguila; Héctor del Risco; Cristina Martí; Sonia Tarazona; Pedro Salguero; Raymond Scott; Alberto Lerma; Ana Alastrue-Agudo; Pablo Bonilla; Jeremy R. B. Newman; et al. (Genome Biology, 2020)
Abstract Recent advances in long-read sequencing solve inaccuracies in alternative transcript identification of full-length transcripts in short-read RNA-Seq data, which encourages the development of methods for isoform-centered functional analysis. Here, we present tappAS, the first framework to enable a comprehensive Functional Iso-Transcriptomics (FIT) analysis, which is effective at revealing the functional impact of context-specific post-transcriptional regulation. tappAS uses isoform-resolved annotation of coding and non-coding functional domains, motifs, and sites, in combination with novel analysis methods to interrogate different aspects of the functional readout of transcript variants and isoform regulation. tappAS software and documentation are available at https://app.tappas.org .